The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12864-021-08140-w
|View full text |Cite|
|
Sign up to set email alerts
|

Methylome and transcriptome analyses of soybean response to bean pyralid larvae

Abstract: Background Bean pyralid is one of the major leaf-feeding insects that affect soybean crops. DNA methylation can control the networks of gene expressions, and it plays an important role in responses to biotic stress. However, at present the genome-wide DNA methylation profile of the soybean resistance to bean pyralid has not been reported so far. Results Using whole-genome bisulfite sequencing (WGBS) and RNA-sequencing (RNA-seq), we analyzed the hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 92 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Choi et al successively reported that MAPK9 might be involved in memory and stress-related neuroplasticity, and might play a key role in hippocampal neurodevelopment during chronic alcohol consumption [38,39]. In addition, MAPK9 was of interest in the development of various diseases at the level of DNA methylation [40,41]. It has been reported that PRKACB played an important role in cell metabolism, gene transcription and cell proliferation, and it was also closely related to miRNA [42].…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al successively reported that MAPK9 might be involved in memory and stress-related neuroplasticity, and might play a key role in hippocampal neurodevelopment during chronic alcohol consumption [38,39]. In addition, MAPK9 was of interest in the development of various diseases at the level of DNA methylation [40,41]. It has been reported that PRKACB played an important role in cell metabolism, gene transcription and cell proliferation, and it was also closely related to miRNA [42].…”
Section: Discussionmentioning
confidence: 99%
“…( D ) Explanatory notes of transcription factors from ( C ). Baumler et at., 2019, [ 36 ]; Dong et al, 2010, [ 37 ]; Wang et al, 2022, [ 38 ]; Zwack et al, 2016, [ 39 ]; Zheng et al, 2019, [ 40 ]; Xing et al, 2008, [ 41 ]; Zeng et al, 2021, [ 42 ]; Noman et al, 2019, [ 43 ]; Wang et al, 2020, [ 44 ]; Geng et al, 2018, [ 45 ]; Fang et al, 2017, [ 46 ]; Zhang et al, 2023, [ 47 ]; Mito et al, 2011, [ 48 ]; Zhuo et al, 2020, [ 49 ]; Li et al, 2022, [ 50 ].…”
Section: Figurementioning
confidence: 99%
“…Correction to: BMC Genomics 22, 836 (2021) https://doi.org/10.1186/s12864-021-08140-w Following publication of the original article [1] it was reported that the authorship panel listed too many corresponding authors. Zu-Dong Sun is the sole corresponding author.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ] it was reported that the authorship panel listed too many corresponding authors. Zu-Dong Sun is the sole corresponding author.…”
mentioning
confidence: 99%